PENGARUH PELAKSANAAN PENILAIAN UNJUK KERJA TERHADAP KEMAMPUAN PSIKOMOTORIK SISWA PADA MATA PELAJARAN PAI DI SMA N 2 TELUK KUANTAN - Isasli Isasli; Sopiatun Nahwiyah; Sarmidin Sarmidin (Universitas Islam Kuantan Singingi, 2020)
This thesis Talks about the influence of the implementation of the work of psychomotor students in schools 2 teluk kuantan . This study aims to know the whereabouts of work and how much influence on psychomotor students in schools 2 teluk kuantan.The methodology consist of a method of observation ,tests and documentation. Respondent in this research was students XI .There are two variables assessment on the research work and psychomotor students .The data analysis techniques used technique gave pearson correlation with the product moment. After the calculation is done, the writer draws conclusions, namely,